WHERE IS SOCIAL CITIZENSHIP HEADING? (FROM MARSHALL TO SEN) (Andamios, Revista de Investigación Social, 2008)
The concept of social citizenship, as formulated by Marshall in the middle of the 20th century, is in crisis. Its most evident sign is the impact of the privatization policies iniciated by neoliberal governments in 1980. This paper attempts to open a debate about its future, which is linked to the examination of what we understand as welfare. In Amartya Sen’s work, it is possible to find patterns that allow us to go in this direction and ask if it is time to move from a welfare focused on covering needs to another whose aim would be the creation of capacities.
Keywords: Welfare; capacities; social citizenship; Marshall; Sen